Achieving a post-growth green economy - Douglas Booth (The White Horse Press, 2020)
A transformation in human values in a ‘post-materialist’ direction by middle-class youth around the world may be setting the stage for a new reality of near-zero economic growth and a sustainable and healthy global biosphere. Evidence from the World Values Survey suggests that a global expansion of post-material values and experiences leads to (1) a reduction in consumption-oriented activities, (2) a shift to more environmentally friendly forms of life that include living at higher, more energy efficient urban densities, and (3) active political support for environmental improvement. Such behavioral shifts provide a foundation for a turn to a slow-growth or even no-growth economy in comparatively affluent countries to the benefit of a healthier global biosphere. To set the stage for a ‘post-growth green economy’ that features climate stability and a substantially reduced ecological footprint, the timing is right for a ‘Green New Deal’ that focuses on de-carbonizing the global economy and has the side-benefit of fostering an economic recovery from the Covid-19 global recession currently underway. The financing of global decarbonization by the world’s wealthiest countries is affordable and could stimulate much needed economic improvements in developing countries by creating within them modern, efficient clean energy systems that can serve as a basis for increased economic prosperity. Such prosperity will in turn accelerate declines in population fertility and result ultimately in reduced global population growth.